The PET-Derived Tumor-to-Liver Standard Uptake Ratio (SUVTLR) Is Superior to Tumor SUVmax in Predicting Tumor Response and Survival After Chemoradiotherapy in Patients With Locally Advanced Esophageal Cancer - Wang, Chunsheng; Zhao, Kewei; Hu, Shanliang; Huang, Yong; Ma, Li; Li, Minghuan; Song, Yipeng (Frontiers in Oncology, 2020)
Background: The maximum standardized uptake values (SUVmax) derived from 18F-fluorodeoxy-glucose positron emission tomography/computed tomography (18F-FDG PET/CT) have some well-known shortcomings in predicting treatment response and prognosis in oncology. The standardized SUVmax with an appropriate reference background may overcome this problem in some instances. This study explored the prognostic value of the tumor-to-liver SUVmax ratio (SUVTLR) and the tumor-to-blood pool SUVmax ratio (SUVTBR) in predicting the objective response (OR) and overall survival (OS) in patients with locally advanced esophageal cancer after concurrent chemoradiotherapy (CCRT). Methods: We retrospectively analyzed 128 newly diagnosed ESCC patients who were treated with CCRT. The SUVmax of primary tumor, SUVTLR, SUVTBR and clinicopathologic features data were analyzed. Univariate and multivariate analyses were used to determine the predictors of tumor response. Survival analysis was performed using the Kaplan–Meier method and Cox proportional hazards model. Results: Receiver operating characteristic (ROC) curve analysis demonstrated that SUVTLR was superior to SUVmax and SUVTBR in predicting treatment response. Univariate and multivariate analyses revealed that advanced tumor stage (hazard ratio [HR]=9.67; 95% CI: 1.15-81.28; P=0.037) and high SUVTLR (HR=21.92; 95% CI: 2.26-212.96; P=0.008) were independent predictors of poor treatment response. Cox regression analysis showed that good clinical tumor response (p<0.014, HR =0.501; 95% CI: 0.288–0.871) was a favorable independent predictive factor for OS, while an advanced tumor stage (p=0.018, HR =1.796; 95% CI: 1.107-2.915) and a high SUVTLR (p<0.002, HR=2.660; 95% CI: 1.425–4.967) were prognostic factors for poor OS. The median OS of patients in the low SUVTLR and high SUVTLR groups was 13.47 versus 19.30 months, respectively. Conclusions: PET-derived SUVTLR is superior to tumor SUVmax and SUVTBR in predicting treatment response and overall survival in patients with ESCC undergoing CCRT. High SUVTLR was an independent predictor of poor treatment response and shorter overall survival.